2015
DOI: 10.1111/jgs.13840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Transthoracic Echocardiogram on Mortality and Surgical Timing in Elderly Adults with Hip Fracture

Abstract: Preoperative TTE was not associated with lower mortality in elderly adults with hip fracture in the short- or long-term postoperative period. TTE was associated with delayed surgical treatment and longer length of stay and resulted in no cardiac intervention (e.g., cardiac catheterization, stent, stress test).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
2
17
1
1
Order By: Relevance
“…This finding is consistent with previous reports that arrhythmia affects perioperative mortality and length of hospital stay [24]. Age was also found to affect short-term mortality [21,[25][26][27]. According to a previous study by Dodd et al [28], the incidence of 30-day mortality is significantly higher in older patients, and several previous studies have also reported that advanced age affects postoperative mortality [29].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with previous reports that arrhythmia affects perioperative mortality and length of hospital stay [24]. Age was also found to affect short-term mortality [21,[25][26][27]. According to a previous study by Dodd et al [28], the incidence of 30-day mortality is significantly higher in older patients, and several previous studies have also reported that advanced age affects postoperative mortality [29].…”
Section: Discussionsupporting
confidence: 90%
“…Luttrell et al evaluated the impact of preoperative TTE on the elderly hip fractures (131 patients with TTE, 563 patients without TTE). They concluded that the patients with preoperative TTE had obvious longer waiting time to surgery [15]. Harun et al…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested to routinely perform an echocardiography in elderly patients with hip fractures [21]. Some authors have reported a benefit of routine echocardiography on mortality after hip fracture surgery [22], where others have not [23,24]. Screening all hip fracture patients with transthoracic echocardiography (TTE) identified in 8% of patients significant aortic stenosis.…”
Section: Discussionmentioning
confidence: 99%